Longitudinal follow-up of biochemical markers of fatigue throughout a sporting season in young elite rugby players - Alaphilippe, A.; Mandigout, S.; Ratel, S.; Bonis, J.; Courteix, D.; Duclos, M. (The Journal of Strength and Conditioning Research, 2012)
The aims of this study were to evaluate links between biochemical markers and competition and training conditions, overtraining questionnaire scores, and anthropometric characteristics of young elite rugby players and to identify evolving profiles of fatigue during the sports season. Twelve elite rugby players were included in the study. The tests were carried out every 15 days over the course of one sporting season from July until March, including the interseason. Changes in body composition parameters, blood biochemistry, and scores on various questionnaires were examined. The majority of the biochemical parameters and subjective variables showed significant variations over time. There were significant positive correlations between overtraining scores and alanine amino transferase (ALAT; r = 0.24, p < 0.05) and creatine phosphokinase (CK; r = 0.3, p < 0.01) levels. In addition, game time was significantly correlated with changes in CK (r = 0.46, p < 0.01), whereas difficult training sessions were significantly correlated with changes in both CK (r = 0.27, p < 0.05) and ALAT (r = 0.33, p < 0.01). We suggest that regular monitoring of these biochemical parameters may provide important information for the coach on the fatigue of rugby players and their perceived difficulty of training.